Tourist-recreational opportunities of the Rokytne district of the Rivne region - Zoya Karpiuk; Yurii Khmeliovskyi; Mykola Pavlushenko; Roman Kacharovskyi (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії, 2018)
There was discovered and analyzed spatial differentiation of tourist recreational resources of Rokytne district, Rivne region: natural, historical and cultural, social and economic. There were reviewed information possibilities of the model of the mapping card of Rokytne district offered by the authors for forming tourist recreational regional addiction, the important elements of which are interesting natural objects, first of all attractive natural landscapes and natural reservoirs: «Kamianyi Brid», «Kut» on river Lʹvy, «Kosykh», «Smolarna» on Stvyz, boulder type moraine belt «Gorby» near the village Staryky, lakes Bile, Bilske, Tuhove, Chorne, reservoirs Osnytske and «Kobyla»; the wealth of flora and fauna, a significant number of unique areas of the natural reserve fund, including hard-to-reach protected bogs «Syra Pogonia» and «Perebrody» of Rivne natural reserve, memorials of nature of national importance «Juzefinska dacha», «Urochyshche Netreba» and famous known outside the region botanical nature monument of local significance «Juzefinska dacha» – the remnants of the former castle manor of the princes of Radziwill; ecologically clear environ-ment; significant historical and cultural heritage: temples and ancient Slavic graves near the villages Bilovizh, Glyne, Rokytne, Juze-finskyi burial ground of thirty burial mounds, historical and architectural monuments, memorials to the dead: victims and liberators during Second World War, in battles in Afghanistan, victims during the Chernobyl tragedy, fighters for independence, Ukrainian statehood, artistic and ethnographic sights; authentic customs and everyday life, the traditions of the local population. There was analyzed the material and technical base of the territory, the state of its infrastructure, the availability of transport. There were de-fined the most appropriate types of tourist recreational activities. The listed opportunities meet the criteria for motivation for the de-velopment of tourism: recreational, ecological and amateur, culturally cognitive, religious pilgrimage, sentimental. The results of these scientific researches are the follows: inverting existing resources and objectively assessing real opportunities, necessary for active promotion of the tourist potential of the district, forming of its recreational attractiveness, optimal territorial organization and tourism planning at the local and regional levels.